Keretapi Tanah Melayu Berhad (KTMB) / Nurul Izzah Azlan, Erlina Mohamad Jaaper and Puteri Najihah Megat Zakaria - Azlan, Nurul Izzah; Mohamad Jaaper, Erlina; Megat Zakaria, Puteri Najihah (2019)
This write up specifically discuss about one component of the Malaysian transportation system .which is the railway Keretapi Tanah Melayu Berhad (KTMB). Being a student we had been traveling with KTM to various locations. We use KTM in our daily life. During this time we have witnessed the progress of ticketing system of KTMB. This paper explains the ticketing system of KTM Komuter. As consumers become more sophisticated, they demand the right services at the right time, right price and at the right place. Today, the major challenge that KTMB faces are loss in revenue. This can be overcome if KTM is willing to make improvement in their ticketing system.